Exploring the self-preparedness of frontline healthcare workers in a low- and middle-income country from a humanitarian context during the COVID-19 pandemic: A constructivist grounded theory study - Khan, Farzana; Azad, Tasnim B.; Bhuyian, Saiduzzaman; Karim, Hasina; Grant, Liz (Frontiers in Public Health, 2023)
Background While research has been conducted on the availability, accessibility, and affordability of personal protective equipment for healthcare workers during the COVID-19 pandemic, little information is available on the ways in which health workers, especially those in humanitarian settings see themselves, and engage in self-preparedness for social, physical, and mental health and practical care in the pandemic. We sought to address this gap. Methods We followed a constructivist grounded theory approach to guide in-depth interviews with 30 frontline doctors, nurses, and community healthcare workers recruited from the Rohingya refugee camps in Bangladesh using the purposive and snowball sampling methods. Analyses were carried out through the identification of codes in three phases: an initial line-by-line open coding, then focused axial coding, and finally selective coding. Findings An emergent-grounded theory of “Navigating Self-Preparedness through Pandemics” was developed as we built a five-phased theoretical framework examining health worker responses with the following pillars: (a) pandemic shock; (b) pandemic awareness; (c) pandemic learning; (d) pandemic resilience, and (e) pandemic resurgence. Interpretation The theory emerged as a realistic, socially, and culturally sensitive COVID-19 strategy to support healthcare workers. Self-preparedness was characterized by two interwoven processes: (1) the experiences of the daily life span of healthcare workers attempting to improve their own protection using all their potential while providing care for patients in a vulnerable setting and time and (2) the inseparable role of physical, psychological, social, and spiritual factors in each stage of learning during the pandemic to achieve better outcomes.